USE OF INNOVATIVE METHODS IN DEVELOPING PROFESSIONAL SKILLS OF STUDENTS (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
Vocational training is a complex and multifaceted process, based on which the opportunities for successful work in a particular profession, personal orientation, professional knowledge, skills, qualifications and professional qualities, work experience are integrated. appears in the effectiveness of innovative methods and technologies in its formation today is great. Students' knowledge and skills are developed through the use of innovative methods in the educational process in order to improve the professional skills of students. In this article, I want to highlight the role of innovative methods and the importance of modern technology in professional development.